Islamic Education and Da’wah Strategies Based on Culture in the Ilir-ilir Song of Sunan Kalijaga - Mulyono Mulyono (FITK UIN Walisongo, 2020)
The purpose of this study is to examine the educational and da’wah strategies based on the culture in the Song Ilir-ilir Sunan Kalijaga. By using library research methods and content analysis techniques, the results as follows: 1) With a cultural approach, Sunan Kalijaga invites and educates the public to embrace Islam as a new religion that came to Java around the 13-15 century AD. 2). Persuasively, Sunan Kalijaga made people aware of Islam by carrying out the five pillars of Islam while leaving all beliefs and deeds prohibited by Islam. 3) With the metaphor of Blimbing (star fruit). Sunan Kalijaga assures people that whoever obeys the commands of Islam, will find peace and happiness in living in this world and the hereafter. Educators and preachers in various events create the Ilir-ilir Song as a cultural-based educational and da’wah strategy that remains popular in the millennial era. AbstrakTujuan penelitian ini untuk mengkaji strategi pendidikan dan dakwah Islam berbasis kultural dalam lagu Ilir-ilir Sunan Kalijaga. Dengan menggunakan metode penelitian kepustakaan (library research) dan teknik analisis isi (content analisys), maka hasilnya dapat disimpulkan berikut: 1) Dengan pendekatan kultural, Sunan Kalijaga mengajak dan mendidik masyarakat untuk memeluk Islam sebagai agama baru yang datang ke tanah Jawa sekitar abad 13-15 M. 2) Secara persuasif, Sunan Kalijaga menyadarkan masyarakat untuk memeluk Islam dengan melaksanakan rukun Islam yang lima seraya meninggalkan segala keyakinan dan perbuatan yang dilarang Islam; 3) Dengan metafora buah blimbing, Sunan Kalijaga menyakinkan masyarakat bahwa barangsiapa yang taat menjalankan perintah Islam, kelak mendapatkan ketentraman dan kebahagiaan hidup di dunia dan di akhirat. Para pendidik maupun juru dakwah dalam berbagai event mengkreasi lagu Ilir-ilir sebagai strategi pendidikan dan dakwah berbasis kultural yang tetap populer di era millineal.